Adherence to Injury Prevention Exercise Programmes in Amateur Adolescent and Adult Football: A Detailed Description of Programme Use from a Randomised Study - Hanna Lindblom; Markus Waldén; Martin Hägglund (SpringerOpen, 2023)
Abstract Background Injury prevention exercise programmes (IPEPs) efficaciously reduce injuries. However, it is challenging to achieve sufficient adherence across a season. The main aim was to describe adherence to IPEPs in three groups of coaches and players partaking in a cluster randomised trial. Secondary aims were to describe perceptions of IPEPs, use of programme material, and overall preventive strategies. Methods This is a sub-study analysing data from a three-armed randomised trial with teams randomised to use either a comprehensive IPEP (extended Knee Control) or an adductor strength programme, and non-randomised teams that already used a self-chosen IPEP regularly at study start (comparison group). Teams were instructed to use their respective intervention across the 2020 football season. Male and female, adolescent (≥ 14 years of age), and adult amateur players took part. Coaches and players responded to weekly and end-of-season questionnaires. Data were presented descriptively. Results Weekly player data were reported by 502 players (weekly response rate 65%), 289 (58%) responded to end-of-season questionnaires. Teams in the extended Knee Control and comparison group used their respective IPEP in 483/529 (91%) and 585/641 (91%) of training sessions, and teams in the adductor group in in 199/315 (63%) sessions. Regarding utilisation fidelity, 42-52% of players in each group used 1-10 repetitions per exercise. Seven out of 17 teams in the adductor group had progressed as recommended in terms of number of repetitions. Two teams (10%) in the extended Knee Control group, and 7/24 of comparison teams used the same exercises across the season. Coaches accessed the IPEPs by different means (printed material, films, workshops, etc.), but half did not use the provided digital material. The players appreciated that the IPEPs could reduce injury risk and that they improved their exercise performance, but disliked that they had less time for football and that the exercises were boring. Forty-nine players had experienced pain during IPEP performance. Conclusions Adherence with the IPEPs was generally high. To meet different coach needs, programme material should be available via different digital and printed resources. The number of players reporting pain during IPEP performance is a noteworthy finding. Trial registration Clinical Trials gov identifier: NCT04272047. Registered February 17, 2020. https://clinicaltrials.gov/ct2/show/NCT04272047 .